Spirometry testing for extracorporeal membrane oxygenation (ECMO) bridge to transplant patients. (2022) - Timofte, Irina; Diaz-Abad, Montserrat; Alghanim, Fahid; Assadi, Jordan; Lau, Christine; Madathil, Ronson; Griffith, Bartley; Herr, Daniel; Iacono, Aldo; Hines, Stella
Abstract: Purpose: ECMO can provide a bridge to transplantation and improve survival for patients with advanced lung disease. Although pulmonary function testing (PFT) is an important component of the lung allocation score (LAS), it is not always feasible on patients requiring ECMO. While generally safe, PFT testing has contraindications and is not recommended in unstable patients. Currently there are no recommendations regarding the performance of spirometry in ECMO patients. Study design: and Methods: We reviewed data on five patients with advanced lung disease requiring ECMO-bridge to transplant. After careful consideration of the theoretical physiologic risks associated with forced expiratory maneuvers, bedside spirometry was performed in order to update the patients' LAS. Results: All patients successfully completed three forced expiratory maneuvers in the seated position with a bedside spirometer. Vital signs and ECMO flow were stable during testing and without complication. In 2 patients who had both a LAS pre and post spirometry, the LAS increased by 3–5 points. Conclusion: Spirometry results are pivotal to organ allocation under current organ sharing protocols. This case series demonstrates that bedside spirometry testing may be performed safely in patients on ECMO awaiting lung transplantation without appreciable side effects, leading to a more accurate LAS score.